Statistical Based Audio Forensic on Identical Microphones - Fajri Kurniawan; Mohd. Shafry Mohd. Rahim; Mohammed S. Khalil; Muhammad Khurram Khan (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Microphone forensics has become a challenging field due to the proliferation of recording devices and explosion in video/audio recording. Video or audio recording helps a criminal investigator to analyze the scene and to collect evidences. In this regards, a robust method is required to assure the originality of some recordings. In this paper, we focus on digital audio forensics and study how to identify the microphone model. Defining microphone model will allow the investigators to conclude integrity of some recordings. We perform statistical analysis on the recording that is collected from two microphones of the same model. Experimental results and analysis indicate that the signal of sound recording of identical microphone is not exactly same and the difference is up to 1% - 3%.